Ethnic composition of schools and school performances in secondary education of Turkish migrant students in 7 countries and 19 European educational systems - Gert-Jan Veerman; Jaap Dronkers (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
This article examines the effect of the ethnic school composition on school performances in secondary education for Turkish students, using both cross-national PISA 2009 and Swiss national PISA 2009 data. We argue how social capital theory beside other theories can explain a part of the ethnic composition effect. We employ three indicators of the ethnic composition of a school: the native share, the share of co-ethnics and the ethnic diversity (we employ a residualized score of diversity on the proportion of migrants). Our results show no effect of the proportion of natives on math performances. Furthermore, we show a negative association between ethnic diversity and math performances. Nevertheless, we find a positive association between ethnic diversity and reading performances in The Netherlands. Children of Turkish decent have higher math performances if they are in an educational system with a larger community of co-ethnics and if they are in an educational system with native students with average higher school performances. Finally we find no association between an early comprehensive labor agreement and math performances.
Keywords: 330; ethnic composition; Turkish migrant students; ethnic diversity; social capital